2006
DOI: 10.1103/physrevb.74.176401
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Charge order inFe2OBO3: AnLSDA+Ustudy”

Abstract: In a recently published paper ͓Phys. Rev. B 72, 014407 ͑2005͔͒, Leonov et al. present an LSDA+ U study of the low temperature monoclinic structure of the iron oxoborate ͑Fe 2 OBO 3 ͒. They report on Fe 2+ -Fe 3+ charge ordering without taking into account recent resonant x-ray scattering experiments, which demonstrate the lack of charge ordering in a closely related oxide such as Fe 3 O 4 . They propose that the charge ordering occurs between equivalent crystallographic sites. First, this result, apart from su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Although we have been unable to assign an accurate value to the charge segregation, we are able to estimate the disproportionation as being between 0.4e − and 0.8e − . Thus we have demonstrated that despite some previous reports to the contrary, 31 Fe 2 OBO 3 is indeed charge ordered, but that the differences between the 3d electronic configuration of inequivalent sites is noninteger. We have demonstrated that under certain conditions we can observe a nonlinearly polarized component to the scattered beam from linearly polarized incident light, and confirmed this conversion using incident circularly polarized light.…”
Section: Discussioncontrasting
confidence: 78%
“…Although we have been unable to assign an accurate value to the charge segregation, we are able to estimate the disproportionation as being between 0.4e − and 0.8e − . Thus we have demonstrated that despite some previous reports to the contrary, 31 Fe 2 OBO 3 is indeed charge ordered, but that the differences between the 3d electronic configuration of inequivalent sites is noninteger. We have demonstrated that under certain conditions we can observe a nonlinearly polarized component to the scattered beam from linearly polarized incident light, and confirmed this conversion using incident circularly polarized light.…”
Section: Discussioncontrasting
confidence: 78%
“…It is natural then to suspect an ordered arrangement of Fe 2+ and Fe 3+ ions (ionic CO), and Fe 2 OBO 3 has been suggested as an example of electrostatically driven CO [6]. However, no experimental evidence of a CO superstructure was found on the available polycrystalline samples, and consequently the occurrence of CO in Fe 2 OBO 3 has been under debate [7].Here, we report the first observation of superstructure reflections in single-crystalline Fe 2 OBO 3 , using X-ray diffraction. Combining structural refinement, Mössbauer spectroscopy, and electronic structure calculations, we establish a diagonal CO configuration.…”
mentioning
confidence: 99%
“…It is natural then to suspect an ordered arrangement of Fe 2+ and Fe 3+ ions (ionic CO), and Fe 2 OBO 3 has been suggested as an example of electrostatically driven CO [6]. However, no experimental evidence of a CO superstructure was found on the available polycrystalline samples, and consequently the occurrence of CO in Fe 2 OBO 3 has been under debate [7].…”
mentioning
confidence: 99%
“…12 However, certain essential issues for this CO state are still in debate. [13][14][15] In this paper we will report on the electronic structure of the CO state in Fe 2 OBO 3 via the first-principles calculations and electron energy-loss spectroscopy (EELS) measurements. In order to understand the essential properties of the CO state, the effects of lattice distortions and on-site Coulomb repulsion are accounted for, respectively, in our investigations.…”
mentioning
confidence: 99%